The practice of medicinal chemistry 2026-02-15T20:52:06+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Aldous, David (David John); Raboisson, Pierre; Rognan, Didier; Wermuth, C. G. (Elsevier Academic Press, 2015)

(untitled)
The Practice of Medicinal Chemistry, Fourth Edition, provides a practical and comprehensive overview of the daily issues facing pharmaceutical researchers and chemists. In addition to its thorough and excellent treatment of basic medicinal chemistry principles, this updated edition has been thoroughly revised to provide new and expanded coverage of the latest technologies and approaches in drug discovery. With in-depth coverage of high content screening, scoring, docking, binding free energy calculations, polypharmacology, QSAR, chemical collections and databases, and much more, this book is the go-to reference for all academic and pharmaceutical researchers who need a complete understanding of medicinal chemistry and its application to drug discovery and development